Mileposts in the Development of Salutogenesis - Lindström, Bengt (Springer International Publishing, 2022)
In this chapter, the author reviews mileposts in the development of the field of salutogenesis from the late 1990s until today. This is a chronology of the meetings, seminars and other events that have provided space and time for the development of salutogenesis as an academic field. This chapter is of historical value and helps describe the global collaborative work that has supported the network of colleagues whose work is in the book.